Influence of Religious Guidance Services in Reducing Anxiety in Pregnant Women - Putu Agus Windu Yasa Bukian; Wayan Sujana (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Pregnancy and childbirth are causes of anxiety experienced by mothers, so there is a need for more specific information or assistance, for example with religious services. This study aims to analyze the effect of religious guidance services provided to pregnant women on the anxiety of pregnant women. The research method uses a quantitative approach with a pre-experimental pre-posttest one group. The population is pregnant women in the village of Kubutambahan with a minimum sample size of 36 respondents. Furthermore, the sampling technique using purposive sampling. The instrument used was a questionnaire regarding the characteristics and anxiety of the mother using the HARS questionnaire. Then, univariate and bivariate analyzes were performed using the compare mean. The results found that there was a decrease in anxiety in pregnant women before and after being given religious guidance services with a mean delta value of 2.1, p value <0.0001 and 95% CI (1.7-2.6). The conclusion is that there is a significant influence from religious services to reduce anxiety in pregnant women in Kubutambahan Village.